2021
DOI: 10.37268/mjphm/vol.21/no.2/art.521
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Reasoned Action to Predict Smoking Intention Among Non-Smoking Secondary School Going Adolescents in Peninsular Malaysia

Abstract: The study aims to determine the relationship of attitude and social-norm with the intention to smoke in the future among non-smoking youth. Data were derived from a study on smoking among form four students in a selected secondary school in Peninsular Malaysia, which utilised a pre-validated questionnaire to obtain data from the selected respondents. Descriptive statistics and structural equation modelling (SEM) were used in data analysis. The study revealed independent variables accounted for 22.6% of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Knowledge and sociodemographic could indirectly influence attitude and subjective norms, which subsequently affect intention (Fishbein & Azjen, 1975). A study demonstrated a noteworthy correlation between subjective norms and the intention to smoke among non-smoking youths (Lim et al, 2021b). The proposed conceptual framework shown in Figure 1 illustrates the source of information as the starting point.…”
Section: Subjective Norm Health Literacy and Health Information-seekingmentioning
confidence: 99%
“…Knowledge and sociodemographic could indirectly influence attitude and subjective norms, which subsequently affect intention (Fishbein & Azjen, 1975). A study demonstrated a noteworthy correlation between subjective norms and the intention to smoke among non-smoking youths (Lim et al, 2021b). The proposed conceptual framework shown in Figure 1 illustrates the source of information as the starting point.…”
Section: Subjective Norm Health Literacy and Health Information-seekingmentioning
confidence: 99%
“…This instrument measures an individual's self-worth by gauging both negative and positive feelings of oneself and can be administered to individuals aged 12 years old and older (21). Numerous studies worldwide have vouched for this scale's reliability and validity (including Malaysia), all establishing that this scale is able to effectively evaluate the self-esteem level of individuals across ethnicities (29). The Malay version of the RSES was used in this research.…”
Section: Instrumentmentioning
confidence: 99%
“…In this study, second-hand smoke exposure indicates a significant highlight when, there is a potential comfort and health issue. The main source of second-hand smoke from smokers who use tobacco products during the study period is second-hand smoke [27]. The health effects of second-hand smoke can vary, including asthmatic attacks [5], [26] [28], particle dispersion that effects eye [8], [24], [26], and respiratory discomfort from nearby non-smoker due to exposure to the tar, nicotine and carbon monoxide [10], [29].…”
Section: Health Status Of Respondents Due To Indoor Exposurementioning
confidence: 99%